2017
DOI: 10.1016/j.bbr.2017.08.017
|View full text |Cite
|
Sign up to set email alerts
|

Developmental suppression of forebrain trkA receptors and attentional capacities in aging rats: A longitudinal study

Abstract: Basal forebrain (BF) cholinergic neurons innervating the cortex regulate cognitive, specifically attentional, processes. Cholinergic atrophy and cognitive decline occur at an accelerated pace in age-related neurodegenerative disorders such as Alzheimer’s disease; however, the mechanism responsible for this phenomenon remains unknown. Here we hypothesized that developmental suppression of nerve growth factor signaling, mediated via tropomyosin-related kinase A (trkA) receptors, would escalate age-related attent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 79 publications
0
6
0
Order By: Relevance
“…Memory formation increases BDNF and p-CREB/CREB in PFC, the hippocampus and amygdala [ 30 ]. Dysfunction or degeneration of BFCNs can lead to cholinergic atrophy and cognitive decline, and affect normal function of the hippocampus; it may be associated with the development of neuroinflammatory components of diseases such as AD [ 31 ]. The nucleus basalis of Meynert (NBM) is a key brain region that is mainly cholinergic.…”
Section: Physiological Function Of Cholinergic Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Memory formation increases BDNF and p-CREB/CREB in PFC, the hippocampus and amygdala [ 30 ]. Dysfunction or degeneration of BFCNs can lead to cholinergic atrophy and cognitive decline, and affect normal function of the hippocampus; it may be associated with the development of neuroinflammatory components of diseases such as AD [ 31 ]. The nucleus basalis of Meynert (NBM) is a key brain region that is mainly cholinergic.…”
Section: Physiological Function Of Cholinergic Systemmentioning
confidence: 99%
“…Cholinergic atrophy and cognitive decline are accelerated in age-related neurodegenerative diseases such as AD [ 31 ]. Glutamate and cholinergic dysfunction are known features of AD [ 51 ].…”
Section: Ad Relation To the Cholinergic Systemmentioning
confidence: 99%
“…Water-regulated young and aged rats were trained in an operant-based sustained attention task (SAT) as previously described ( Demeter et al, 2008 ; McGaughy & Sarter, 1995 ; St Peters et al, 2011 ; Yegla & Parikh, 2017 ). Animals were initially autoshaped using an FR-1 reinforcement schedule to attain the lever press response and succeeding water reward (0.02 mL).…”
Section: Methodsmentioning
confidence: 99%
“…Each session was analyzed in terms of the proportion of hits (h = h/[h+m]*100) for each signal length, proportion of correct rejections (cr = cr/[cr+fa]*100), and proportion of omissions ([omitted trials/total trials]*100. The overall measure of attentional performance was calculated as a performance score (SAT/dSAT score) using the formula: (h − fa)/[2(h + fa) − (h + fa) 2 ] as described previously ( Demeter et al, 2008 ; McGaughy & Sarter, 1995 ; St Peters et al, 2011 ; Yegla & Parikh, 2017 ). SAT/dSAT scores vary from +1.0 to −1.0; a score of +1.0 indicated that all responses on signal and non-signal trials were correct, 0 indicated the inability to discern signal from non-signal events, and −1.0 indicated that all responses were misses/false alarms.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation